Методика оценки информативности маршрута движения - Valentin Vladimirovich Vasil’Ev; Maxim Yur’evich Manzin (Вестник СибАДИ)
The article develops the estimation technique of informative content of an isolated irregularity and a track section as a whole. This method allows predicting the value of the average speed that provides the driver's ability to process and realize the information on ambient traffic conditions. The authors reveal the impact of the motor field vehicle design on the information received by the driver in the course of the structure of the motion law. The article can be useful to researchers, engineers and technicians in handling trial of the vehicles, dealing with practical aspects of tests and evaluation of ergonomic features of the vehicles such as usability of the driver's compartment.